Le locus standi dans les actions d'intérêt public et la relator action : l'empire de la common law en droit québécois - Gélinas, Fabien (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
The duality of the sources of Quebec law poses special problems for the jurist who must determine the juridical norm applicable to a given situation. He must work within the appropriate body of norms and, at the same time, propose a solution which is acceptable in practice. The authority of common law in Quebec extends to limits which are not well-established and not likely soon to be clarified. Starting from the vexed question of standing in public interest actions, the author elaborates on the applicability of common law with respect to the Quebec Code of Civil Procedure. The article first discusses briefly the principles of common law which have traditionally governed standing in public interest actions, together with the corresponding legislative framework established in Quebec. Emphasis is given to the rights and duties of the Attorney General, especially in the area of relator proceedings. The author questions the soundness of interpreting the Code of Civil Procedure as if it were an ordinary statute in a common law system. Bearing in mind its underlying purpose, he proposes a protectionist interpretation of the Code of Civil Procedure, less susceptible to the infiltration of common law.